Public and private insurance with costly transactions - Giuseppe Bertola; Winfried Koeniger (Institute for the Study of Labor (IZA), 2010)
We characterize how public insurance schemes are constrained by hidden financial transactions. When non-exclusive private insurance entails increasing unit transaction costs, public transfers are only partly offset by hidden private transactions, and can influence consumption allocation. We show that efficient transfer schemes should take into account the impact of insurance on unobservable effort and saving choices as well as the relative cost of public and private insurance technologies. We provide suggestive evidence for the empirical relevance of these results by inspecting the cross-country relationship between available indicators of insurance transaction costs and variation in public and private insurance.
Keywords: E21; D82; H21; G22; 330; public transfers; private insurance; moral hazard; transaction costs; Privatversicherung; Versicherung; Transaktionskosten; Moral Hazard; Öffentlicher Transfer; Theorie